Developing ESP Material for University Agriculture Students in Indonesia - Wennyta, Wennyta; Fitri, Nurul; Indriani, Devi; Haswendra, Aditya Reza (Universitas Batanghari Jambi, 2025)
In today's increasingly advanced, interconnected, and open world, job seekers face competition not only on a regional or national level but also internationally. English proficiency is a highly valuable asset for university graduates because English is the international language used by all parties worldwide. Graduates from the Faculty of Agriculture in Indonesia are no exception. They face the demand for English skills, especially those that are directly applicable to their chosen field of study, to be competitive in the job market. English for Specific Purposes (ESP) is the answer to this problem. ESP can greatly assist agriculture students in mastering vocabulary, topics, articles, and other contexts specific to their field. This need will be further explored in detail through a needs analysis to understand the extent of students' needs regarding the four language skills: reading, writing, listening, and speaking. The results of this needs analysis will be combined with the existing curriculum in the Faculty of Agriculture as a source of topics and articles to be included in the materials. This will then be reviewed by experts using the Likert scale to ensure the quality of the agricultural ESP learning materials.